AN ANALYSIS OF SETTING IN UNCHARTED MOVIE - Mokhammad Firman Alamsyah; Deswandito Dwi Saptanto (Praniti: Jurnal Pendidikan, Bahasa, dan Sastra, 2025)
The film "Uncharted" delivers an extraordinary visual experience with its adventurous and mysterious settings. Against the backdrop of exotic locations worldwide, the audience is taken on a journey to iconic places that play an integral role in the narrative. For instance, a striking setting is the untouched wilderness, where towering trees, lush vegetation, and hidden tunnels create an atmosphere of mystery and tension. The protagonist, Nathan Drake, must navigate through the challenges of the wild, solving hidden puzzles along the way. Furthermore, the film transports viewers to ancient cities with grand architecture and an authentic atmosphere. Through meticulous visual details, the audience is immersed in the beauty and marvels of archaeological wonders. Scenes set in these ancient cities add a touch of history and culture, adding depth to the unfolding story. Not only that, but "Uncharted" also showcases settings involving open waters, such as vast oceans and tumultuous rivers. The protagonist's bravery in facing challenges amidst a stormy sea or navigating thrilling waterfalls adds a gripping action element to the narrative. Overall, the film's settings are not merely visual backdrops but also integral characters in the story. With a strong and detailed portrayal, "Uncharted" successfully takes its audience on an epic journey that combines the beauty of nature, history, and unforgettable adventures.`